The art of supervision: Role of supervisory skills in developing teacher capacity - Makin, Mislinah; Abdullah, Zuraidah; Shafee, Salwati (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
This study seeks to identify the role of supervisory skills in building teacher capacity through instructional supervision. Data gathered in the study were analysed using the SPSS version 21.0 software which involved descriptive statistical method, mean and standard deviation. Data were also analysed using Structural Equation Modelling to look at the relationship between constructs supervisory skills and teacher capacity. For the purpose of the research, 390 respondents who are secondary school teachers in the state of Selangor, Malaysia were involved as sample of the study. The findings of the study indicate that in instructional supervision practices, the level of the supervisory skills construct is at high level. On the other hand, the level of teacher capacity is at moderate level. The findings of the SEM analysis also indicate that there is significant positive relationship between the supervisory skills construct and the construct of teacher capacity. The findings of the study will help the Ministry of Education and school administrators in particular, to focus on improving the practice of supervision in schools. This can be enhanced by focusing on building the prerequisite knowledge and skills of supervision in improving the quality of the implementation of classroom supervision. This is especially important in the attempt to help teachers strengthen their instructional practices by building teacher capacity. All in all, improving instructional practices and learning outcomes are vital as it is in line with the aspirations of the 21st century learning.